Investigation and Remediation of the Cavern in the Vrata Tunnel on the Zagreb – Rijeka Highway (Croatia) - Mladen Garašić; Meho Saša Kocačević; Danijela Jurić-Kaćunić (Acta Carsologica, 2010)
In the Dinaric karst system in Croatia some 11500 speleological objects have been explored so far, more than 1000 of which were discovered during construction works. Such speleological objects without natural entrance on the terrain surface (which are called „caverns“) have been discovered on the construction sites of the highways. Over the past twenty years they have been systematically investigated and treated. A special kind of remediation was conducted in the cavern’s large hall of the „Vrata“ tunnel on the Zagreb – Rijeka highway. Due to size, shape, cavern’s position and hydrogeological parameters within the karst system it was necessary to design and construct a 58 m bridge over the cavern. In addition, the cavern’s vault had to be reinforced and stabilized, as the overburden was very thin. The beam-and –stringer grid with special anchors was used. The cavern’s rehabilitation in the „Vrata“ tunnel was a unique undertaking, and the bridge (without piers) is the cavern’s longest bridge in the world.